Nanocellulose, a Versatile Green Platform: From Biosources to Materials and Their Applications - Thomas, Bejoy; Raj, Midhun C; B, Athira K; H, Rubiyah M; Joy, Jithin; Moores, Audrey; Drisko, Glenna L; Sanchez, Clément (Chemical reviews, 2018)
With increasing environmental and ecological concerns due to the use of petroleum-based chemicals and products, the synthesis of fine chemicals and functional materials from natural resources is of great public value. Nanocellulose may prove to be one of the most promising green materials of modern times due to its intrinsic properties, renewability, and abundance. In this review, we present nanocellulose-based materials from sourcing, synthesis, and surface modification of nanocellulose, to materials formation and applications. Nanocellulose can be sourced from biomass, plants, or bacteria, relying on fairly simple, scalable, and efficient isolation techniques. Mechanical, chemical, and enzymatic treatments, or a combination of these, can be used to extract nanocellulose from natural sources. The properties of nanocellulose are dependent on the source, the isolation technique, and potential subsequent surface transformations. Nanocellulose surface modification techniques are typically used to introduce either charged or hydrophobic moieties, and include amidation, esterification, etherification, silylation, polymerization, urethanization, sulfonation, and phosphorylation. Nanocellulose has excellent strength, high Young's modulus, biocompatibility, and tunable self-assembly, thixotropic, and photonic properties, which are essential for the applications of this material. Nanocellulose participates in the fabrication of a large range of nanomaterials and nanocomposites, including those based on polymers, metals, metal oxides, and carbon. In particular, nanocellulose complements organic-based materials, where it imparts its mechanical properties to the composite. Nanocellulose is a promising material whenever material strength, flexibility, and/or specific nanostructuration are required. Applications include functional paper, optoelectronics, and antibacterial coatings, packaging, mechanically reinforced polymer composites, tissue scaffolds, drug delivery, biosensors, energy storage, catalysis, environmental remediation, and electrochemically controlled separation. Phosphorylated nanocellulose is a particularly interesting material, spanning a surprising set of applications in various dimensions including bone scaffolds, adsorbents, and flame retardants and as a support for the heterogenization of homogeneous catalysts.